Cue competition influences biconditional discrimination. Issue 2 (February 2019) - Byrom, Nicola C; Murphy, Robin A
When multiple cues are presented in compound and trained to predict an outcome, the cues may compete for association with an outcome. However, if both cues are necessary for solution of the discrimination, then competition might be expected to interfere with the solution of the discrimination. We consider how unequal stimulus salience influences learning in configural discriminations, where no individual stimulus predicts the outcome. We compared two hypotheses: (1) salience modulation minimises the initial imbalance in salience and (2) unequal stimulus salience will impair acquisition of configural discriminations. We assessed the effect of varying stimulus salience in a biconditional discrimination (AX+, AY−, BX−, BY+). Across two experiments, we found stronger discrimination when stimuli had matched, rather than mismatched, salience, supporting our second hypothesis. We discuss the implications of this finding for Mackintosh's model of selective attention, modified elemental models and configural models of learning.